The current security threat landscape. - Santos, Omar (LiveLessons., 2016)
"The security landscape is in constant flux. Adversaries used to take months or years to compromise a network, but today only a few minutes--or even in some cases, seconds--is needed to compromise and exfiltrate data. Your only defense is to gain the knowledge you need to fully understand and prepare for the current threat landscape and how these threats are evolving. This one-hour primer on security threats in today's world will set you on the road to understanding and accessing the tools you need to understand what is happening within the threat landscape, and specifically how to begin defending your network. You will also gain insight into the underground activities that adversaries are involved in, and what return of investment they seek after exploitation."--Resource description page.